It jes' happened : when Bill Traylor started to draw - Tate, Don.; Christie, R. Gregory, 1971- (New York : Lee & Low Books, 2012)
A biography of Bill Traylor, a former slave who began to draw pictures--based on his recollections of rural and urban life--at the age of 83.
Includes bibliographical references.
Publisher's Weekly, February 2012.
Kirkus Starred, March 2012.
Publisher's Weekly.
Kirkus Starred.
4.5
Keywords: Traylor, Bill, -- 1854-1949 -- Juvenile literature; Traylor, Bill, -- 1854-1949.; Traylor, Bill, -- 1854-1949.; African American painters -- United States -- Biography -- Juvenile literature; Folk artists -- United States -- Biography -- Juvenile literature; African Americans -- Biography; Painters; Folk artists; African Americans -- Biography; Painters -- United States -- Biography; Folk artists -- Biography; African American artists -- Biography; Folk art -- United States; African Americans -- Alabama -- Biography; Alabama -- Biography -- Juvenile literature; Alabama; Alabama -- Biography; Picture books for children